2020
DOI: 10.18781/r.mex.fit.2008-1
|View full text |Cite
|
Sign up to set email alerts
|

Gains in recurrent selection cycles for grain yield and resistance to head smut in maize

Abstract: El basidiomiceto <em>Sporisorium reilianum</em> f. sp. <em>zeae</em> infecta al cultivo de maíz y causa importantes pérdidas en regiones donde existen condiciones propicias para el desarrollo de la enfermedad. En este trabajo se evaluó la respuesta a la selección de seis ciclos de selección recurrente de maíces de endospermo blanco y cinco ciclos de maíces de endospermo amarillo para caracteres agronómicos deseables, rendimiento de grano y resistencia al carbón de la espiga. Los diferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Ayiga-Aluba et al [8] observed the gain per cycle from C 0 to C 2 was 8.35%, C 0 to C 1 was 6.94% and C 1 to C 2 was 1.32%. Diaz-Ramirez et al [10] studied their response to selection of six and five cycles of selection in white and yellow populations through S 1 recurrent selection. For grain yield there was an increase of 0.3 and 0.6 t ha -1 cycle -1 for white and yellow populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayiga-Aluba et al [8] observed the gain per cycle from C 0 to C 2 was 8.35%, C 0 to C 1 was 6.94% and C 1 to C 2 was 1.32%. Diaz-Ramirez et al [10] studied their response to selection of six and five cycles of selection in white and yellow populations through S 1 recurrent selection. For grain yield there was an increase of 0.3 and 0.6 t ha -1 cycle -1 for white and yellow populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Average genetic gain per cycle was persuading for grain yield (13.93%). Diaz-Ramirez et al [10] stated that the response to selection of six and five cycles of selection in a white and a yellow endosperm maize populations improved through S 1 recurrent selection. A genetic gain in grain yield of 272.9 and 620 kg ha -1 /cycle -1 for the white and yellow endosperm populations, respectively.…”
Section: Introductionmentioning
confidence: 99%